Influencing factors of venous thromboembolism in cancer patients and effect analysis of early nursing interventions (癌症患者静脉血栓栓塞症影响因素分析及早期护理干预效果观察) - GUAN Lin (管玲); YU Jie (于洁) (中西医结合护理)
Objective To analyze the influencing factors of venous thromboembolism (VTE) in cancer patients and investigate the effect of early nursing interventions on prevention of VTE. Methods A total of 115 cancer patients were included as research objects. The incidence of VTE was observed, and levels of coagulation-related indicators, Wells scale and Caprini risk assessment scale of patients with VTE and without VET were compared. According the nursing interventions, patients were divided into two groups: 57 cases in mechanical method group and 58 cases in early nursing intervention group. The incidence of VTE was compared between two groups. Results The incidence of VTE was 17. 39%(20/115). There was no significant difference in the incidence of VTE between patients aged under 70 and over 70(P＞0. 05). The levels of D-dimer and thrombin-antithrombin III complex (TAT) in the patient with VTE was higher than those of patients without VTE (P＜0. 05). There was no significant in thrombin time (TT), activated partial thromboplastin time (aPTT), prothrombin time (PT) Wells scale and Caprini risk assessment scale between patients with and without VTE. Lower incidence of VTE was reported in patient who received early nursing combined with mechanical prevention(12. 07%) compared with that in patient received mechanical prevention only(22. 81%). Conclusion More attention should be paid to prevention of VTE in cancer patients, especially those with increased levels of D-dimer and TAT, and early nursing interventions should be carried out to reduce the risk of VTE (目的 分析癌症患者静脉血栓栓塞症(VTE)的影响因素, 探讨早期护理干预效果。方法 本研究纳入115例癌症患者, 调查不同基线资料癌症患者VTE的发生率, 对比VTE患者与无VTE患者凝血相关指标、Wells评分和Caprini评分。根据接受干预措施不同将患者分为两组, 其中57例患者接受常规机械预防措施, 58例患者接受早期护理干预联合机械预防措施, 比较两组静VTE的发生率。结果 共20(17. 39%)例患者发生VTE。≥70岁与＜70岁患者VTE发生率差异无统计学意义(P＞0. 05)。VTE患者与无VTE患者的D-二聚体、凝血酶-抗凝血酶Ⅲ复合物(TAT)水平差异有统计学意义(P＜0. 05), 凝血酶时间(TT)、活化部分凝血活酶时间(APTT)、凝血酶原时间(PT)、Wells评分和Caprini评分差异无统计学意义(P＞0. 05)。接受护理干预联合机械预防措施的患者中有7(12. 07%)例患者发生VTE, 仅接受机械预防措施的患者中13(22. 81%)例发生VTE。结论 应重视癌症患者, 尤其是D-二聚体和TAT水平升高患者静脉血栓栓塞性疾病的预防, 并积极采取早期护理干预措施。)